2012
DOI: 10.1111/j.1532-5415.2012.04054.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Frailty in Community‐Dwelling Older Persons: A Systematic Review

Abstract: Frailty is common in later life, but different operationalization of frailty status results in widely differing prevalence between studies. Improving the comparability of epidemiological and clinical studies constitutes an important step forward.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

113
1,725
43
97

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,358 publications
(2,089 citation statements)
references
References 29 publications
113
1,725
43
97
Order By: Relevance
“…In patients with significant cardiovascular disease, the prevalence of frailty has been shown to be as high as 60% 2. In this study of older Australian MI patients, 15% of STEMI patients and 34% of NSTEMI patients were classified as frail.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In patients with significant cardiovascular disease, the prevalence of frailty has been shown to be as high as 60% 2. In this study of older Australian MI patients, 15% of STEMI patients and 34% of NSTEMI patients were classified as frail.…”
Section: Discussionmentioning
confidence: 73%
“…The overall prevalence of frailty in adults aged ≥65 years has been estimated at ≈10%. However, in patients with significant cardiovascular disease, the prevalence may be as high as 60% 2. Frailty has been associated with increased major adverse cardiac events after myocardial infarction (MI) 3, 4, 5, 6.…”
Section: Introductionmentioning
confidence: 99%
“…The different measures of frailty include physical phenotype,37 clinical functional assessments,22 and functional assessments in combination with disability or laboratory values; these have all been studied in the general population 7. The prevalence of frailty assessed by physical phenotype is 9.9% and 13.6% when using a broader definition in adults >64 years of age 7. In comparison, a study of 152 cardiac surgery patients using 3 different frailty scales reported a prevalence of 20% to 46%, depending on the method chosen to define frailty 14.…”
Section: Discussionmentioning
confidence: 99%
“…Frailty is a common syndrome described as a diminished resiliency in response to stress as a result of decreased physiological reserve, increased burden of comorbidities, and altered multisystem homeostasis 6. Frailty increases susceptibility to adverse health outcomes and contributes to the difference between chronological and physiological age 7. It is associated with increased mortality, surgical site infections, length of hospital stay, increased healthcare expenditure, and readmission rates in patients presenting for a variety of major noncardiac surgeries 8, 9, 10, 11, 12.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to previous studies that tested phenotypic frailty, this result is within the interval detected, which ranges from 4.0 to 59.1%. 31 However, the prevalence of frailty varies widely due to the definition of the concept (which has implications on the assessment instruments used) and the population studied. In the present study, more than half of the sample (50.9%) was classified as pre-frail, which is a similar result to those recorded in earlier studies.…”
Section: Discussionmentioning
confidence: 99%